Chest Pain in the Cancer Patient - Sara Tyebally; Aruni Ghose; Daniel H Chen; Aderonke T Abiodun; Arjun K Ghosh (European Cardiology Review)
Chest pain is one of the most common presenting symptoms in patients seeking care from a physician. Risk assessment tools and scores have facilitated prompt diagnosis and optimal management in these patients; however, it is unclear as to whether a standardised approach can adequately triage chest pain in cancer patients and survivors. This is of concern because cancer patients are often at an increased risk of cardiovascular mortality and morbidity given the shared risk factors between cancer and cardiovascular disease, compounded by the fact that certain anti-cancer therapies are associated with an increased risk of cardiovascular events that can persist for weeks and even years after treatment. This article describes the underlying mechanisms of the most common causes of chest pain in cancer patients with an emphasis on how their management may differ to that of non-cancer patients with chest pain. It will also highlight the role of the cardio-oncology team, who can aid in identifying cancer therapy-related cardiovascular side-effects and provide optimal multidisciplinary care for these patients.